Discerning citation patterns in dominant BME literature streams: Lessons for BME scholars - J. B. Arbaugh; Alvin Hwang; Jeffrey J. McNally; Charles J. Fornaciari; Lisa A. Burke-Smalley (Organization Management Journal (OMJ), 2021)
Purpose: This paper aims to compare the nature of three different business and management education (BME) research streams (online/blended learning, entrepreneurship education and experiential learning), along with their citation sources to draw insights on their support and legitimacy bases, with lessons on improving such support and legitimacy for the streams and the wider BME research field. Design/methodology/approach: The authors analyze the nature of three BME research streams and their citation sources through tests of differences across streams. Findings: The three streams differ in research foci and approaches such as the use of managerial samples in experiential learning, quantitative studies in online/blended education and literature reviews in entrepreneurship education. They also differ in sources of legitimacy recognition and avenues for mobilization of support. The underlying literature development pattern of the experiential learning stream indicates a need for BME scholars to identify and build on each other's work. Research limitations/implications: Identification of different research bases and key supporting literature in the different streams shows important core articles that are useful to build research in each stream. Practical implications: Readers will understand the different research bases supporting the three research streams, along with their targeted audience and practice implications. Social implications: The discovery of different support bases for the three different streams helps identify the network of authors and relationships that have been built in each stream. Originality/value: According to the authors' knowledge, this paper is the first to uncover differences in nature and citation sources of the three continuously growing BME research streams with recommendations on ways to improve the support of the three streams.
Keywords: 650; Bibliometrics; Experiential learning; Entrepreneurship education; Management education; Citation patterns; Online/blended learning